Tensile strength of suture material for oral and periodontal surgery: A narrative review (Research, Society and Development, 2022)
Objetive: To provide a narrative review of the current literature on tensile strength of different sutures materials employed in oral and periodontal surgery. Materials and methods: MESH terms have been used to search relevant literature electronically in the PubMed, Science Direct, Semantic Scholar, Scopus, Scielo, SpringerLink and Google Scholar databases.  This review has analyzed studies on monofilament, multifilament, absorbable, and non absorbable suture's materials. Conclusions: The best tensile strength properties may be  found in  polypropylene, polyglycolic acid, polydioxanone suture's material due to their properties.  This data should be considered so that the operator chooses  the suture material taking into account their tensile strength behavior for  periodontal or oral  surgeries where sutures need to be retained for longer periods . However, further studies are needed to understand tensile strength in different procedures and the variability of clinical situations.